Pengaruh Pemberian Omlet Daun Katuk Terhadap Kejadian Kurang Energi Kronis (KEK) pada Ibu Hamil di Puskesmas Bukit Kemuning - Sephia, Sephia; Astuti, Dewi Woro; Hervidea, Radella (CV. Rayyan Dwi Bharata, 2024)
Chronic Energy Deficiency (CED) is a nutritional problem in pregnant women which is currently a nutritional problem in the world. The World Health Organization (WHO) explains that the prevalence of Chronic Energy Deficiency (KEK) in general in pregnancy is 35% to 75% (Abadi Putri, 2020). Lampung Province, KEK pregnant women is 13.62%, while in North Lampung Regency it is 9.92% (Riskesdas, 2018). The aim of this research is to find out whether there is an effect of giving katuk leaf omlet on the incidence of chronic energy deficiency (CED) in pregnant women at the Bukit Kemuning Community Health Center. This type of research uses a quasi-experimental method (quassy experiment) with a one group pretest-posttest design. The population of this study was all pregnant women with Chronic Energy Deficiency (CED), namely 16 pregnant women. The sampling technique uses the total sampling method. Data were collected using observation sheets and body weight measurements using digital scales and LILA measurements using LILA tape. The statistical tests used were the paired test to the T-Test and the Wilcoxcon Test. The results of the study. Giving katuk leaf omlet affected the weight of KEK pregnant women at the Bukit Kemuning Community Health Center (p-value = 0.000) and giving katuk leaf omelette had an effect on the LILA of KEK pregnant women in Bukit Kemuning Community Health Center (p-value = 0.027). Giving katuk leaf omelette for 30 days had an effect on the incidence of KEK at the Bukit Kemuning Community Health Center. In this research, it is hoped that health workers can provide mothers with the ability to consume nutritious food, and can introduce other local PMT which are consumed by pregnant women. Pregnant women with CED must consume food according to their needs to meet their nutritional intake.